STUDI PERBANDINGAN PENGGUNAAN BEKISTING KONVENSIONAL DENGAN BEKISTING SEMI SISTEM (TABLE FORM) PADA PROYEK GEDUNG BERTINGKAT BANYAK - Agustanto, Kukuh (BENTANG : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2013)
Along with technological developments, the construction work also changes it is marked by many innovations in the construction process. Form work for concrete mold in construction is one example that is also changing the assembly system, manufactured and assembled formwork used in the project area, but now there formwork is made in work shop. Writing of this thesis to analyze the comparative use of conventional formwork formwork system spring (table form) which models the sample on four projects. From the data obtained were analyzed using fixed and variables parameters are different for each type of formwork . Fixed variables include the price of materials, equipment rental, wage labor, and material help. While other variables include the price of the work unit, the total price of the work , the rest of the material , the percentage of the price of concrete work. Analysis of the result obtained that the wage semi form work system is 14.9 % more efficient, more efficient work of the unit price 17.65 %, the total price of 18.46 % more efficient work, the percentage of the price of concrete is more efficient 18.42 %, and the remaining material system is more efficient semi form work 48.38 % when compared with the use of form work konvensional. Keywords: formwork, table form, bekisting